Ancillaries in the aviation industry : importance, trends, going digital - Bogdan Avram (Expert journal of marketing, 2017)
In 2016, the global airline industry reached almost 70 billion dollars in ancillaries (up from 60 billion dollars in 2015), while the ancillary revenues on a global scale reached a 10% share of overall airline revenue, according to Ideaworks, a consulting firm that measures airline ancillary revenues. This research aims to investigate how airline companies use ancillaries in their favour to add value and revenue sources to the booking engine, offer flexibility to their passengers, increase revenues and customer satisfaction, interact with passengers at all touch points to create commercial opportunities and differentiate their brand.
2758454-9; 2344-6773; Expert journal of marketing; 778946770